(untitled) (The International Journal for Scientific Research, 2024)
This study aimed to clarify the extent of the impact of the career guidance program with its dimensions (quality of guidance programs, duration of the program, content of the program, training and guidance methods) in improving the skill of selection and the concept of self-development in the Human Resources Development Fund in the Kingdom of Saudi Arabia. The study community represented the beneficiaries of the career guidance programs in the Human Resources Development Fund. Due to the difficulty of conducting a comprehensive census of all members of the study community, the study used the simple random sampling method to collect data. The number of study sample members reached 394 individuals who answered the questionnaire questions. The results of the study showed a statistically significant impact of the career guidance program with its dimensions (quality of guidance programs, duration of the program, content of the program, training and guidance methods) in improving the skill of selection and the concept of self-development in the Human Resources Development Fund in the Kingdom of Saudi Arabia. The study recommended the need to work on providing all financial, technological and technical resources to the Human Resources Development Fund to increase its ability to implement the goals that are consistent with the Kingdom’s Vision 2030 related to human resources, and to increase the level of awareness of individuals of the importance of self-development and increase their skills and abilities to develop and improve their work.